2019
DOI: 10.3390/ma12111778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicone Oil Viscosity and Carbonyl Iron Particle Weight Fraction and Size on Yield Stress for Magnetorheological Grease Based on a New Preparation Technique

Abstract: This paper investigated the effects of silicone oil viscosity (SOV) and carbonyl iron particle (CIP) weight fraction and size on dynamic yield stress for magnetorheological (MR) grease. The MR grease samples were prepared using orthogonal array L9 on the basis of a new preparation technology. The shear rheological tests were undertaken using a rotational shear rheometer and yield stress was obtained based on the Bingham fluid model. It was found that CIP fractions ranging from 65 wt% to 75 wt% and SOV varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Consequently, performance would decrease, especially under the influence of low magnetic field strengths. Recently, Wang et al [ 13 ] optimized a method to fabricate MRG through an ANOVA of many parameters such as CIP fraction and size, and silicone oil viscosity. They found that the optimum yield stress can be obtained by manipulating the fraction of CIPs and silicone oil viscosity, but the influence of CIP size was negligible.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, performance would decrease, especially under the influence of low magnetic field strengths. Recently, Wang et al [ 13 ] optimized a method to fabricate MRG through an ANOVA of many parameters such as CIP fraction and size, and silicone oil viscosity. They found that the optimum yield stress can be obtained by manipulating the fraction of CIPs and silicone oil viscosity, but the influence of CIP size was negligible.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon shows that all MRF samples without a magnetic field tend to behave like Newtonian fluids [16]. However, when a magnetic field was applied, the MRF had a steady shear stress value in each shear rate range and behaved like a Bingham fluid [43].…”
Section: Resultsmentioning
confidence: 93%
“…This phenomenon shows that all MRF samples without a magnetic field tend to behave like Newtonian fluids [16]. However, when a magnetic field was applied, the MRF had a steady shear stress value in each shear rate range and behaved like a Bingham fluid [43]. The viscosity of the three CIP-based MRF samples as a function of shear rate at different magnetic flux densities is shown in Figure 6.…”
Section: Resultsmentioning
confidence: 95%
“…Consequently, it would reduce its performance especially under the in uence of low magnetic eld strengths. Recently, Wang et al 12 , has optimized the method to fabricate MRG through an ANOVA analysis by many parameters such as CIPs fraction and size, and silicone oil viscosity. They found that the optimum yield stress could be obtained by manipulating the CIPs fraction and silicone oil viscosity, but the in uence of CIPs size was negligible.…”
Section: Introductionmentioning
confidence: 99%